COMPUTERIZED SYSTEM MEDICINES ON INVENTORY CIPULIR PERMAI JAKARTA PHARMACIES - Yohanes Keluli; Ir. Irwan Bastian, SKom, MM (Jurnal Sistem Informasi, 1997)
Pharmacies invetory data processing on the previous Cipulir Permai still done manually will often lead to delays resulting primarily concerns information required reports. In this case it is necessary to use a computer as a tool in data pro cessing inventory at Cipulir Pharmacies Permai. Based on existing information systems in Pharmacies Cipulir Permai and with respect to information originating from outside Pharmacies Cipulir, can be compiled inventory data processing systems that support t he evaluation, analysis, and appropriate decision-making process.